Navigating Patriarchy and Institutional Barriers: An Autoethnographic Exploration of Women’s Entrepreneurship in Nepal through the Story of Bhagawati Subedi - Subedi, Bhagawati (Dogadakedar Journal of Academics, 2025)
This study explores the multi-dimensional challenges faced by women entrepreneurs in Nepal through the autoethnographic narrative of mine. It reveals how a woman who transitioned from teaching aspirations to running a furniture business amidst social, cultural, and institutional constraints. The article by using different theories critically examines how patriarchal social norms and informal institutional practices hinder women’s economic participation. There theories include feminist theory, institutional theory, and concepts such as role congruity, emotional labor, and cultural capital. My story exposes that I had academic qualifications and family as well as societal expectations for job, and expectation for entrepreneurial ship due to the gendered prejudices and thus it illustrates the persistence of hegemonic masculinity. The research highlights the intersectionality of gender, culture, and bureaucracy on the one hand, and reveals how emotional resilience and identity management are crucial for survival in hostile environments, on the other. Additionally, the study exposes the persistence of traditional economic models that nuances women entrepreneur in patriarchal contexts. By situating my lived experience on the base of the above-mentioned theories this research contributes knowledge on gender inequality as evidence to create pressure for inclusive and supportive policy reform for women in Nepal and similar contexts.